ENHACING STUDENTS’ WRITING IN RECOUNT TEXT THROUGH INDIRECT FEEDBACK - Pratiwi Yunianti, Eka (Universitas Aisyah Pringsewu, 2022)
This study aims to find differences in students' writing skills and aspects of writing that increase after applying indirect feedback as a technique. The method in this research is One group pretest-posttest. A total of 32 students from class X.10 were selected as the sample in this study. The data collection tool is a recount text writing test. The results showed that the t-value was higher than the critical value of (8.420>2.040), and the two-way test turned into large (zero.000 <0.05). Meanwhile, the aspect of students' writing that significantly improved became vocabulary because the increase became 4.26. therefore, it is possible to be concluded that there are differences in students' writing skills after applying indirect feedback as a technique. This research may help increase college students' writing skills, specifically in vocabulary.